Genetic and neural mechanisms of sleep disorders in children with autism spectrum disorder: a review - Ji, Qi; Li, Si-Jia; Zhao, Jun-Bo; Xiong, Yun; Du, Xiao-Hui; Wang, Chun-Xiang; Lu, Li-Ming; Tan, Jing-Yao; Zhu, Zhi-Ru (Frontiers in Psychiatry, 2023)
Background: The incidence of sleep disorders in children with autism spectrum disorder (ASD) is very high. Sleep disorders can exacerbate the development of ASD and impose a heavy burden on families and society. The pathological mechanism of sleep disorders in autism is complex, but gene mutations and neural abnormalities may be involved. Methods: In this review, we examined literature addressing the genetic and neural mechanisms of sleep disorders in children with ASD. The databases PubMed and Scopus were searched for eligible studies published between 2013 and 2023. Results: Prolonged awakenings of children with ASD may be caused by the following processes. Mutations in the MECP2, VGAT and SLC6A1 genes can decrease GABA inhibition on neurons in the locus coeruleus, leading to hyperactivity of noradrenergic neurons and prolonged awakenings in children with ASD. Mutations in the HRH1, HRH2, and HRH3 genes heighten the expression of histamine receptors in the posterior hypothalamus, potentially intensifying histamine's ability to promote arousal. Mutations in the KCNQ3 and PCDH10 genes cause atypical modulation of amygdala impact on orexinergic neurons, potentially causing hyperexcitability of the hypothalamic orexin system. Mutations in the AHI1, ARHGEF10, UBE3A, and SLC6A3 genes affect dopamine synthesis, catabolism, and reuptake processes, which can elevate dopamine concentrations in the midbrain. Secondly, non-rapid eye movement sleep disorder is closely related to the lack of butyric acid, iron deficiency and dysfunction of the thalamic reticular nucleus induced by PTCHD1 gene alterations. Thirdly, mutations in the HTR2A, SLC6A4, MAOA, MAOB, TPH2, VMATs, SHANK3 and CADPS2 genes induce structural and functional abnormalities of the dorsal raphe nucleus (DRN) and amygdala, which may disturb REM sleep. In addition, the decrease in melatonin levels caused by ASMT, MTNR1A, and MTNR1B gene mutations, along with functional abnormalities of basal forebrain cholinergic neurons, may lead to abnormal sleep-wake rhythm transitions. Conclusion: Our review revealed that the functional and structural abnormalities of sleep-wake related neural circuits induced by gene mutations are strongly correlated with sleep disorders in children with ASD. Exploring the neural mechanisms of sleep disorders and the underlying genetic pathology in children with ASD is significant for further studies of therapy.